Implementasi Keselamatan dan Kesehatan Kerja (K3) sebagai Upaya Perlindungan Buruh Pabrik Penggilingan Padi dalam Menghadapi Risiko Kerja - Ayi Miranda, (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
The rice processing industry (rice milling) plays a vital role in the economy, yet it often neglects Occupational Safety and Health (OHS), placing workers at significant risk. This study aims to describe the implementation of OHS as a means of protecting rice mill workers from various occupational risks. This study used a qualitative descriptive method, with data collection techniques including in-depth interviews, observation, and documentation studies. The results indicate that OHS implementation in rice mills remains suboptimal, particularly in the provision and use of Personal Protective Equipment (PPE), minimal OHS socialization and training, and unstructured hazard elimination and risk assessment. The main occupational risks faced include physical hazards (noise, vibration, temperature), chemical hazards (rice dust), and ergonomic hazards (manual lifting). This study concludes that the role of OHS in protecting workers has not been fully realized, and recommends stronger intervention by employers and government oversight.